Fracture resistance of different implant supported ceramic abutment/crown systems - Cemal Aydın; Handan Yılmaz; Seçil Karakoca Nemli; Merve Bankoğlu Güngör (Istanbul University, 2019)
Purpose The purpose of this study was to investigate the fracture resistance and failure modes of different non-aged and aged abutment/crown systems. Materials and Methods One hundred dental implants (diameter 4.3 mm and length 11.5 mm) were restored with five abutment/crown systems: G1: a lithium disilicate hybrid abutment crown, G2: a lithium disilicate crown cemented on a lithium disilicate hybrid abutment, G3: a lithium disilicate crown cemented on a zirconia hybrid abutment, G4: a direct veneer porcelain layering on a zirconia hybrid abutment, and G5: a lithium disilicate crown cemented on a prefabricated all-zirconia abutment. Each group was divided into two groups (n=10) as control (non-aged) and thermomechanically aged. The fracture resistance test was performed. Failures during the aging process and after the fracture resistance test were examined. Results Both of the factors (restoration type and aging) affected the fracture resistance values and there was not an interaction between the factors (p>0.05). When fracture resistance values were compared regardless of aging, the highest values were observed in G3 and G4, respectively (p<0.05). When comparing the fracture resistance values, regardless of the restoration type, the aged group showed a significant lower fracture resistance value than control group (p<0.05). Conclusion A titanium base enhanced the fracture resistance of zirconia abutments. Thermomechanical aging decreased the fracture resistance of the tested ceramic abutment/crown systems. The major failure mode was the abutment fracture.